Research progress on the correlation between biological rhythms and the blood-brain barrier after ischemic stroke - Liao, Yuanchen; Luo, Lei; Ma, Qiang; Gao, Xiaofeng; Chen, Yao; Yan, Siyang; He, Menghao; Liu, Lijuan; Zhou, Desheng (Frontiers in Neurology, 2025)
Biological rhythms play a critical role in regulating human physiology and have been implicated in the onset, progression, and recovery of ischemic stroke (IS). This review summarizes recent experimental and clinical studies that associate circadian regulation with post-stroke blood–brain barrier (BBB) repair, focusing on the role of molecular clock components. Core clock components, including BMAL1 and CLOCK, influence BBB integrity by regulating tight junction protein expression, angiogenesis, neuroimmune responses, and neuroendocrine signaling. Finally, we discuss emerging chronotherapeutic strategies that integrate circadian biology into stroke rehabilitation.